Jaringan Sosial dan Variasi Pekerjaan Para Migran di Kota Samarinda - Izzah, Atiyatul (UI Scholars Hub, 2011)
Migration in Samarinda has always had an important role in longterm changes within social processes; corresponding to historical and political trends rather than just to short-term economic calculation. In Indonesia, migration was seen as a crucial survival strategy. Migration has been a crucial factor contributing to economic growth and poverty reduction either in the origin and the destination. Moreover, it has been known that within Samarinda, peasants tend to keep social ties with the place of their origin using circular migration as a transitional step to explore opportunities in urban settings and to expand livelihood security during the transitional periods before possible permanent migration is established. Samarinda growthits as represent of new city character In Indonesia.